Memories, citizenship, and interculturality in contexts of Violence and resistance in Latin America - LUQUE BRAZÁN, José Carlos; ARROYO SALINAS, Claudia (Utopía y Praxis Latinoamericana, 2025)
The dossier Cultural Heritage, Memories, Citizenship and Interculturality in Contexts of Violence and Resistance in Latin America brings together a wide range of reflections and case studies that reveal how heritage and memory are not static objects but dynamic and contested fields of meaning, struggle, and transformation. In contexts marked by structural, symbolic, and material violence, these processes emerge as practices of resistance, identity affirmation, and collective resilience. The contributions address theoretical genealogies of memory, representations of gender and violence in Mexican cinema, youth perceptions of democracy in Guerrero, community-based heritage practices, indigenous religiosity, community radio, feminist visual narratives, school memories of bullying, archives of resistance, and human rights struggles. They are complemented by critical analyses of neoliberal symbolic violence, urban artistic expressions in Acapulco, and decolonial perspectives on heritage. Together, the articles map out the disputes, practices, and imaginaries through which Latin America faces its violent past and present while reimagining its future. This dossier thus constitutes an interdisciplinary and situated space that highlights the power of memory and cultural heritage as political tools for justice, intercultural dialogue, and the construction of alternative forms of citizenship.